Saneamento básico goiano: uma proposta de intervenção regulatória para o aumento da eficiência e eficácia dos serviços oferecidos à população - Guimarães, Patrick Souto (2018)
The provision of water and sewage services is fundamental to the development of society, as it is closely related to public health, people's quality of life and the income of a nation. In the Brazilian case, despite the promulgation of Federal Law 11,445 / 2007 (Law on National Guidelines for Basic Sanitation), universal access to these services is still a reality distant, which is also observed in the state of Goiás. The purpose of this work was to propose methodologies for tariff revisions and readjustments in the different regions of Goiás in order to improve the efficiency and effectiveness of sanitation in the state. In specific terms, this work evaluated the efficiency in the state using as methodology the DEA model, based on data from the SNIS 2016 (national information system on sanitation), in addition to the analysis of the efficiency measured by the index of water and sewage service. The results indicated that there is a possibility of increased efficiency in all the analyzed regions, with a better allocation of productive inputs capable of bringing water to a further 231 thousand people, and sewage treatment to a further 75 thousand, representing an increase in the service index of water of 3.71% and in the index of service of sewage in 1.21% in all the state of Goiás. When analyzing the investment history, it was observed that the regions with the best rates of water supply are also the regions that received most of the volume of financial resources, and the region of Centro Goiano was the largest beneficiary, which received 56.46% of the total investment in the period from 2000 to 2016, and where currently the highest index of basic sanitation in the state are found. In conclusion, the study proposes to intervene the need of the Goiás Regulatory Agency (Agência Goiana de Regulação, Controle e Fiscalização de Serviços Públicos - AGR) to increase the number of regulatory agreement contracts with municipalities, to assist municipalities and their sanitation providers to participate in information retrieval from the SNIS and, as a major objective of this work, it was proposed to use economic and financial mechanisms, through new tariff revisions and adjustments, using the Fator X methodology, to encourage sanitation service providers to use productive resources more efficiently and effectively, in accordance with the universalization.